Assessment of Students’ Achievement in Life Science through Different Evaluation Strategies: Examining the Influence of Teacher Competence and Teaching Effectiveness - Banerjee, Sarmila (INDIAN EDUCATIONAL REVIEW, 2017)
In the present paper efforts were made to study the assessment of achievement through different evaluation strategies. Twenty-one secondary schools of four boards of Birbhum and Burdwan districts of West Bengal were selected through stratified random sampling technique. The Boards were: West Bengal Board of Secondary Education (W.B.B.SE), Visva Bharati(V.B), Indian Certificate of Secondary Education (I.C.S.E) and Central Board of Secondary Education (C.B.S.E). A total of 564 students from Class VIII participated in the study. All the Life-Science teachers were also taken as sample. Tools used were standardised tests (i) ‘Teacher Competence Scale’ developed by Passi & Lalitha, 7-point scale, (ii a) A standardised ‘Teacher Effectiveness Scale’ by U. Kulsum, a 5-point scale and a self-assessment questionnaire, (b) Observation Schedule to measure the teaching effectiveness, (iii) An achievement test for Class VIII (Pre-test in Life Science). Statistics used were Mean, S.D., t-value, One-way ANOVA and Interaction analysis. The role of teacher competence and teaching effectiveness in high achievement (in Life-Science) irrespective of the different evaluation strategies used were examined. The study gave indications about the relative suitability of these strategies used in measuring the students’ performances in Life science subject.